Clinical and radiographic features of moyamoya disease in patients with both cerebral ischaemia and haemorrhage. (April 2013) - Hishikawa, Tomohito; Tokunaga, Koji; Sugiu, Kenji; Date, Isao
Abstract Objectives. Patients with moyamoya disease (MMD) very rarely develop both cerebral ischaemia and haemorrhage. The aim of this study was to clarify the clinical and radiographic features of MMD in patients who presented with both ischaemia and haemorrhage, compared with MMD patients who presented with one or the other. Materials and methods. The records of 92 consecutive patients with MMD were reviewed. These patients were divided into three groups, according to the type of presentation: ischaemic presentation (Group I); haemorrhagic presentation (Group H); and haemorrhagic-ischaemic presentation (Group H-I). The patient characteristics, areas of infarction, and angiographic findings were evaluated. Results. Seventy-six (82%) of the 92 patients were categorised as Group I, 7 (8%) as Group H, and 9 (10%) as Group H-I. Median follow-up periods for Group H-I was 55 months (IQR, 36–116 months). There were eight females in Group H-I, in which the median age was 30 years. Of the nine cases in Group H-I, six presented with cerebral haemorrhage as the precedent event and three had complications during the acute phase. In Group H-I, the prevalence of posterior cerebral artery (PCA) lesions was high (42%) and infarctions were most frequently found in PCA-related areas. Conclusions. The presence of steno-occlusive PCA lesions may be of pathogenic importance in MMD patients who develop both cerebral ischaemia and haemorrhage. The prevalence of this type of stroke in MMD patients is higher than expected, and further investigation in clinical settings is thus warranted.